1980
DOI: 10.1080/00288233.1980.10425368
|View full text |Cite
|
Sign up to set email alerts
|

Growth and solasodine production bySolanum aviculareandSolanum laciniatumunder moisture stress at different temperatures

Abstract: Cloned plants were grown in growth-chambers for 82 days under day/night temperatures of Is o / 10°, 20°/10°, 20°/1 So, 2So/1So, and 2So/20°C. Dry matter yields were greatest at 2SoC daytime temperatures. Solanum laciniatum also grew well in the coldest conditions, whereas growth of S. aviculare was depressed at the two lowest temperatures.Solasodine concentrations in leaves and particularly in sterns were lower at the warrnest temperatures. Total solasodine yield per plant remained approximately constant becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
2

Year Published

1983
1983
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…C'est une observation de pratique courante que les fins de production en serre, comme au champ, donnent parfois des fruits inacceptables sur le plan gustatif. Juvik et al (1982), Man et al (1980), Yaniv et al (1984) ont montré que les saponosides interviennent dans la réponse des plantes aux variations climatiques. De plus, Defago (1977) et Rowan et al (1983) (Fig.…”
unclassified
See 1 more Smart Citation
“…C'est une observation de pratique courante que les fins de production en serre, comme au champ, donnent parfois des fruits inacceptables sur le plan gustatif. Juvik et al (1982), Man et al (1980), Yaniv et al (1984) ont montré que les saponosides interviennent dans la réponse des plantes aux variations climatiques. De plus, Defago (1977) et Rowan et al (1983) (Fig.…”
unclassified
“…1) comme pour les SNA (Fig. 2) (Heftmann, 1983;Man et al, 1980). Khristov (1975) (Daunay, 1986;Pochard 1973, Pochard & Serieys, 1974Pochard & Cornillon, 1975) (Moutot, 1976 …”
unclassified
“…Also, growth chamber studies by Mann et al (1980) have indicated that night temperatures of 10°C suppress solasodine yield S . aviculare but not S .…”
Section: Received 1 April 1982; Revision 17 December 1982mentioning
confidence: 99%
“…To establish S. laciniatum as a crop species, influences of environmental factors and cultivation have been studied in various climatic zones (MANN et al 1980, BHARATI and CHATTERjEE 1986, KRUG 1989.…”
mentioning
confidence: 99%